Revealing the Symbolic Meaning of the Telek Jumpai Dance within the Belief System of the Jumpai Village Community - Yuliastari, Komang Novi; Pratiwi, Nuning Indah; Antari, Ni Putu Bayu Widhi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study explores the symbolic meanings embedded in the sacred Telek Jumpai Dance performed in Jumpai Village, Klungkung, Bali. The problem addressed in this research arises from the limited understanding of the symbolic functions of its movements and ritual properties, despite its long-standing role in maintaining spiritual balance within the community. The study aims to identify and interpret the symbolic meanings of the dance through the perspectives of local cultural actors. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews with ten informants selected via purposive sampling, and documentation of ritual performances. The findings reveal that each component of the dance such as the white mask, fan, headdress, and core movements acts as a symbolic medium in the communication between the physical (sekala) and spiritual (niskala) realms. Movements like nyalud, nyeregseg ngemapat, aras-arasan, and ngotes represent purification, protection, balance, and spiritual alertness. The community perceives Telek Jumpai not merely as an artistic tradition but as a sacred cultural identity, functioning as a guardian symbol, a unifying force, and a transmitter of ancestral values to younger generations.